MSMEs’ go digital assistance as an effort to support MSMEs’ upgrading program in Banyuasin Regency - Dwi Mirani; Januar Eko Aryansah; Farisha Sestri Musdalifah; Muhammad Yusuf Abror; Krisna Murti (Community Empowerment, 2022)
The Covid-19 pandemic has had a significant impact on Indonesian economic activities, including micro, small, and medium enterprises (MSMEs). MSME actors need a variety of innovations to survive this pandemic, one of which is adapting by moving their business to the digital realm. The majority of the people in Sungai Pinang Village, Rambutan District, Banyuasin Regency, South Sumatra, are farmers, laborers, and entrepreneurs. However, businesspeople in this village are still unfamiliar with how to use technology to digitally market their products. This service program aims to introduce MSME actors to digital marketing and assist them in doing so. Visitations and counseling about digital marketing, as well as direct practice marketing products through digital channels, are the method of this program. Then, after interviewing MSME actors who had participated in the program, follow-up activities were carried out. The outcomes of this program include increased business actors' knowledge and enthusiasm for using digital marketing in sales.